Simultaneous Determination of Carotenoids and Chlorophylls by the HPLC-UV-VIS Method in Soybean Seeds - Berhane Sibhatu Gebregziabher; Shengrui Zhang; Jie Qi; Muhammad Azam; Suprio Ghosh; Yue Feng; Yuanyuan Huai; Jing Li; Bin Li; Junming Sun (Agronomy, 2021)
Soybean contains nutritional bioactive compounds, including carotenoids associated with human health benefits. Carotenoids are applicable in pharmaceuticals/nutreceuticals, cosmetic, and mainly food industries. However, an efficient and accurate method for carotenoid and chlorophyll detection and quantification has not yet been developed and validated for soybean seeds. The need for a rapid and reliable analysis method has become increasingly important. Thus, this study was initiated to develop and validate a simple, rapid, and selective reversed-phase high-performance liquid chromatographic (RP-HPLC) method for the simultaneous determination of lutein, zeaxanthin, α-carotene, β–carotene, β–cryptoxanthin, and chlorophyll–a and –b in soybean flour sample (100.00 mg) extracted using ethanol-acetone (1:1) solvents at a volume of 1.50 mL. Interestingly, the effective separation technique was achieved using the mobile phases of methyl tert-butyl ether, methanol containing 10 mM ammonium acetate, and water delivered at a 0.90 mL min−1 flow rate through a C30YMC Carotenoid (250 × 4.6 mm I.D., S-5 µm) column coupled with a UV-VIS detector set at 450 nm. The detector response was linear from 0.05–30.00 μg mL−1 with a coefficient of determination (R2) of 0.9993–0.9999. The validated method was sensitive with a detection limit (LOD) of 0.0051–0.0300 μg mL−1 and 0.0155–0.0909 μg mL−1 for the quantification limit (LOQ). The recovery values were from 83.12–106.58%, and the repeatability precision ranged from 1.25–4.20% and 0.15–0.81% for the method and system, respectively. The method showed adequate precision with a relative standard deviation smaller than 3.00%. This method was also found to be applicable for profiling carotenoids and chlorophylls in other legumes. In summary, this method was successfully implemented for qualitative and quantitative determination of major carotenoids and chlorophylls in soybean and other legume seeds, which are beneficial to food industry and quality breeding programs to meet human nutrition demands globally.